Data Dissemination in Mobile Wireless Sensor Network Using Trajectory-Based Network Coding - Lingzhi Li; Shukui Zhang; Zhe Yang; Yanqin Zhu (International Journal of Distributed Sensor Networks)
With GPS devices spreading, more mobile nodes are guided by the navigation systems to select better paths. The performance of mobile networks can be improved with the navigation information in nodes. In this paper, we propose a trajectory-based network coding (TBNC) method to disseminate data in mobile wireless sensor network (MWSN). It is designed according to the characteristics of MWSN and is appropriate for the mobile nodes that share anonymously its GPS pretrajectory for the higher bandwidth. Data are disseminated in the topology that is predicted on the basis of the trajectory information. Network coding is used to adapt for the dynamics velocity of mobile nodes. Simulation results show that TBNC is able to cut down 1/2 overhead messages of PRoPHET when mobile nodes share GPS trajectory. It improves the reliability and scalability of MWSN.